Cognitive Bias in Forensic Science - Aditi Borkar (Institute Of computer Science (IOCS), 2023)
Within the realm of forensic science, there has been a notable surge in recognition of the role of human cognition. This has led to a more comprehensive understanding of the limitations and weaknesses of human decision-making when faced with ambiguity, and how they can impact the admissibility and trustworthiness of forensic research. These limitations are often caused by motivational or cognitive biases, which have led to misidentifications and, consequently, wrongful convictions of innocent individuals. It is critical to address these concerns given the significant impact that forensic science has on society. This article delves into the issue of prejudice and its potential impact on the opinions of forensic professionals in criminal cases, as well as the dangers of bias in several forensic science fields, including fingerprint examination, trace evidence, bullet comparison, and DNA analysis. The essay posits that several factors, such as the quality and clarity of forensic evidence, contextual case information, and subjective interpretation of forensic analysis, can contribute to prejudice. To mitigate bias, various strategies such as blind testing, blind verification, independent review, linear sequential unmasking (LSU), and the filler control approach are recommended. The article evaluates the benefits and drawbacks of these tactics and suggests cross-examination questions that may reveal bias in forensic examination.